Development of a core patient-reported outcome set for use in HIV care at the individual patient level in Montreal: protocol for a two-phased multimethod project - Bertrand Lebouché; Karine Lacombe; David Lessard; Kim Engler; Romain Palich (BMJ Open)
Introduction There is international interest in using patient-reported outcome measures in HIV care to improve the well-being of people with HIV, but the prioritisation of specific outcomes and measures remains unclear. This project’s objective is to engage both people with HIV and healthcare, social and community service providers to develop a French and English-language core set of patient-reported outcomes and measures for use in HIV care at the patient level in Montreal (Canada).Methods and analysis This multimethod project will follow guidance from the Core Outcome Measures in Effectiveness Trials Initiative and involve two phases. Phase 1 will see the selection of the core set of outcomes (ie, the health concepts to target) and include a rapid scoping review to inform a Delphi study with a panel of 50 people with HIV and providers in Montreal. It will end with a multidisciplinary consensus meeting to make final decisions on the outcomes. Phase 2 will be devoted to choosing the measures to assess the selected outcomes. It will include a systematic search for instruments, an appraisal of the quality and feasibility of the identified instruments and a consensus meeting for the final selection.Ethics and dissemination Research ethics board (REB) approval was obtained on 9 December 2024, from the institutional REB of the Research Institute of the McGill University Health Centre (reference number: 2024-9695). Findings will primarily be disseminated to (1) healthcare and social service providers through academic rounds and a provincial continuing education programme for HIV clinicians; (2) to people with HIV through partner community organisations and (3) a range of stakeholders at local, national and international conferences and through peer-reviewed publications.